Parallelism of circadian rhythmicity of salivary and serum cortisol concentration in normal dogs - Giannetto, Claudia; Fazio, Francesco; Assenza, Anna; Alberghina, Daniela; Panzera, Michele; Piccione, Giuseppe (Journal of Applied Biomedicine, 2014)
To evaluate parallel circadian rhythms in salivary and serum cortisol concentrations during 48-h period, sampling was performed in six clinically healthy dogs of various breeds housed under natural photoperiod in spring (sunrise 05:20, sunset 20:20). Saliva and blood samples were taken every 3 h for a 48-h period to determine the daily changes in salivary and serum cortisol concentrations. The relationship between salivary and serum cortisol level was determined as well. In the two-day period of monitoring, salivary and serum cortisol concentrations showed the same trend. Their levels started to increase at sunrise and reached their peak in the middle of the photophase. Both parameters showed a high robustness of rhythm. A positive correlation between salivary and serum cortisol concentration was observed during the day 1 and 2. Acrophase and robustness of rhythm showed no statistically significant difference between salivary and serum cortisol concentrations. We can claim that salivary cortisol, a measure of free cortisol, follows the circadian rhythm of serum cortisol. Therefore, saliva sampling is a valid and non-invasive technique useful in chronomedicine to estimate free cortisol.
Keywords: cirkadiánní rytmus; Hydrocortisone; Circadian Rhythm; statistika jako téma; psi; sliny; sérum; Saliva; Animals; Statistics as Topic; Dogs; hydrokortison; zvířata; Serum